Controlling capital? Legal restrictions and the asset composition of international financial flows - Mahir Binici; Michael Hutchison; Martin Schindler (University of California, Santa Cruz Institute for International Economics (SCIIE), 2009)
Legal restrictions on international capital movements are imposed in many countries in an attempt to (partially) insulate their economies from abroad and pursue some degree of domestic policy independence. But is the imposition of capital controls effective in achieving these goals? We investigate this issue from a new angle by linking de jure restrictions on three specific asset categories of outflows and inflows with the corresponding component of capital flows. The analysis is based on a novel panel data set of capital controls data, disaggregated by asset class and by inflows/outflows, and covering 74 countries during 1995-2005. Using panel LSDV regressions, and including a host of well-known determinants of capital flows, we estimate a model of capital flows with four categories: equity-like flows (including FDI) and debt for both capital inflows and capital outflows. The estimated effects of capital controls vary markedly with the type of controls imposed: they are binding on capital outflows (debt, equity and FDI); have no apparent effect on capital inflows of various types; and are less effective in low and middle-income countries. Moreover, there are no apparent substitution effects so that controls on debt and equity outflows change the volume and composition of capital flows as well as the net flow of capital in each asset class. The large differences across asset categories in the effects of capital controls suggest that the common use of aggregate capital control indicators can be misleading.
Keywords: F21; F32; F36; 330; capital controls; capital flows; financial integration; Kapitalverkehrspolitik; Wirkungsanalyse; Kapitalmobilität; Welt